Horizontal orientation of zygomorphic flowers: significance for rain protection and pollen transfer. (27th November 2020) - Yu, Y.‐M.; Li, X.‐X.; Xie, D.; Wang, H.
Abstract: Floral traits are recognized to have evolved under selection for abiotic and biotic factors. Complex zygomorphic flowers usually face horizontally. It has been proved that a horizontal orientation facilitates pollinator recognition and pollination efficiency, but its significance in adaptation to abiotic factors remains unknown. The floral orientation of Abelia × grandiflora naturally varies around horizontal (with an angle of −30 to +33° between the floral main axis and the horizontal). We examined whether three different floral orientations affected flower thermal conditions, response to rain and pollination. Results showed that floral orientation had no effect on diurnal variations in flower temperature. The anthers of all three flower orientations were wetted by rainfall, but the inclined upward‐facing flowers contained significantly more rainwater. The horizontal flowers received significantly higher visitation by hawkmoths and had a higher stigmatic pollen load. In contrast, the upward flower orientation reduced pollination precision, while downward‐facing flowers had decreased pollinator attraction. This study indicates that horizontal flowers may have evolved as a trade‐off between rain protection and pollination. Zygomorphic flowers that deviate from a horizontal orientation may have lower fitness because of flower flooding by rainwater and decreased pollen transfer. Abstract : Horizontal orientation of zygomorphic flowers functioned to protect flowers against rain and promote pollen transfer, revealing that floral orientation may evolved as a trade‐off of biotic and abiotic selection pressures.